Emotional intelligence among nurses in a general hospital setting in Jeddah, Saudi Arabia - Alhakami, Ibrahim Yahya; Baker, Omar Ghazi (Frontiers in Medicine, 2025)
AimEmotional intelligence (EI) is a prerequisite of nursing practice. It significantly affects the wellbeing and quality of the provided services. The literature is scarce regarding the EI levels of Saudi Arabia’s nursing professionals. Therefore, this study aims to assess EI levels and explore influencing factors among nurses in a general hospital in Jeddah, Saudi Arabia.MethodsA cross-sectional design was used involving a convenience sample of 80 registered nurses, and using the Trait Emotional Intelligence Questionnaire Short Form (TEIQue SF) tool for the collection of data. Data were analyzed through ANOVA and independent sample t-test at a p-value of < 0.05.ResultsThe results indicated a moderate TEIQue global score (3.3 ± 0.33), with wellbeing scoring highest (3.7 ± 0.38), followed by sociability (3.3 ± 0.42). In constrast, self-control (3.2 ± 0.37) and emotionality (3.1 ± 0.41) received comparatively lower scores. Female nurses had significantly higher scores of wellbeing, and non-Saudi nurses presented high scores of wellbeing (3.7 ± 0.37) and emotionality (3.2 ± 0.46). Less work experience was associated with a higher global score (3.4 ± 0.40). The regression analysis further revealed a high global score (3.6 ± 0.35) among nurses in the obstetric department.ConclusionNurses demonstrated a moderate level of EI, with wellbeing receiving the highest score, followed by sociability. Gender, nationality, and department were identified as influencing factors on EI levels. These findings emphasize the importance of EI-specific training programs to improve self-control and emotionality. Further longitudinal studies are needed to explore the effects of EI interventions on the skills of nurses and the quality of care of patients.